Vulnerability to poverty in the Philippines: An examination of trends from 2003 to 2015 - Jose Ramon G. Albert; Jana Flor V. Vizmanos (Philippine Institute for Development Studies (PIDS), 2018)
The reduction of poverty is at the heart of the development agenda both nationally and globally. This is reflected in the Philippine Development Plan, as well as in the worldwide commitment toward the Sustainable Development Goals. While the measurement of poverty is ex post and thus, public interventions are directed at helping those who have been identified as poor, the government must broaden the scope of assessments and take account of the dynamics in poverty in public policy. A critical dimension to poverty dynamics is vulnerability which conceptually pertains to the risk of future poverty. This study continued previous work that involves estimating the vulnerability level of households to income poverty using a modified probit model incorporating income and other poverty data sourced from the Family Income and Expenditure Survey, as well as the country's official poverty lines. The vulnerability assessment in this study provides inputs to forward-looking interventions that build the resilience of households to future poverty. The study makes a case for the need to make use of both poverty and vulnerability estimates in programs and come up with differentiated actions for those highly vulnerable and relatively vulnerable.
Keywords: 330; vulnerability; poverty; highly vulnerable; relatively vulnerable; risk; resilience